Prototype Alat Pengering Sarang Walet menggunakan Arduino Nano Berbasis Website - Faruq Ferdinan Syah; Zamah Sari; Luqman Hakim (Universitas Muhammadiyah Malang, 2026)
Bird's nest has a high economy, especially in the health and beauty industry. One of the important steps in maintaining product quality before being marketed is the process of drying the bird's nest. For the process of drying the bird's nest, a more efficient solution is needed. This is because traditional drying methods are often inefficient, take a long time, and depend on the temperature and humidity in the environment. The purpose of this study is to design and develop a prototype of an Arduino Nano-based bird's nest dryer integrated with a web-based system. This tool is equipped with two PTC heaters as heat sources and a DHT22 sensor to measure temperature and humidity. In addition, this system has two levels of shelves to accommodate more bird's nests in one drying cycle. Users can view the temperature and humidity in real time and monitor the drying process remotely via the website. After determining the specified setpoint temperature, the bird's nest drying process is set automatically. The Arduino Nano microcontroller will receive data from the sensor. This data is then processed and displayed in a web interface. This web-based system gives users the ability to monitor the tool without having to be near the device. The test results show that this tool can dry bird's nest with higher efficiency than traditional methods. In addition, the user-friendly interface allows users to monitor the drying process easily. It is hoped that this system will help swiftlet farmers increase productivity and maintain the quality of their nests.